Binding the Strong Man: A Political Reading of Mark's Story of Jesus. By Ched Myers - Rowland, Christopher (The journal of theological studies, 2009)
I don’t know what Walter Wink meant by his endorsement that Ched Myers's book is ‘quite simply the most important commentary on a book of Scripture since Barth's Romans’, but it is entirely appropriate. Myers's commentary on the Gospel of Mark is very different in many respects from Barth's ‘Romans’, but in one crucial respect it is similar. It embodies what Barth considered should be included in a commentary in the preface to the second edition of his Romans commentary—not just linguistic and historical information but an exegetical struggle to make sense of the text.